Exploring the gap between notified and diagnosed cases of Food- borne Diseases: evidence from a time-trend analysis in Italy - Capodici, Angelo; Lenzi, Jacopo; Cavagnis, Sara; Ricci, Matteo; De Dominicis, Francesco; Ambretti, Simone; Gabrielli, Liliana; Galli, Silvia; Lazzarotto, Tiziana; Resi, Davide (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Background. Foodborne diseases are a major global public health concern, causing significant morbidity and mortality worldwide. The COVID-19 pandemic has had widespread effects on various aspects of life, including the food supply chain, potentially impacting the incidence of foodborne diseases. This study aims to analyze the differences between notified and diagnosed cases and investigate the potential impact of the COVID-19 pandemic on foodborne diseases in the metropolitan area of Bologna, Italy. Study Design. A retrospective time trend analysis from two databases was conducted. Methods. The Local Health Authority of Bologna collected data re/Emilia-Romagna Region on the infectious disease reporting system over a six-year period (2017-2022), which included three years of the COVID-19 pandemic. This data was compared with information collected during the same period at the microbiology laboratory serving the entire metropolitan area of Bologna. Statistical methods included percent change calculations, binomial tests, annual averages, gender and age stratification, and trend analysis with regression. Results. An increase (+34.4%, P-value ≤ 0.01) in notified cases during the pandemic - compared to the pre-pandemic period - was found. However, no differences were observed in diagnosed cases when comparing the two periods. The year 2021 saw a significant increase in reported cases of foodborne diseases among schoolers (+300.0%) and workers (+133.3%) compared to 2020. On the other hand, diagnosed cases decreased significantly in 2020 (-19.1%, P